ANALYSIS OF CARDIOVASCULAR HEMODYNAMIC CHANGES IN AUTOIMMUNE THYROIDITIS USING ULTRASONIC ECHOCARDIOGRAPHY (Conferencea, 2024)
Autoimmune thyroiditis (AIT) is a chronic disease characterized by gradual onset, non-specific early symptoms, and slow progression with increasing destructive processes in the thyroid gland. AIT is one of the most prevalent thyroid gland diseases and often accompanies hemodynamic changes affecting the structure and function of the heart. Altered thyroid hormone levels lead to dysmetabolic changes that disrupt structural and functional relationships in various organs, especially in the cardiovascular system. Clinical manifestations of cardiovascular disorders in hypothyroidism include polymorphic chest pain and exertional dyspnea against a background of varied and non-specific symptoms. Literature analysis and clinical observations of patients with hypothyroidism, particularly subclinical forms that often mask cardiovascular pathology, underscore the need for focused study and development of diagnostic, treatment, and prognostic approaches for hemodynamic changes in these patients. This study aims to identify and analyze morphofunctional changes in the heart of patients with different AIT phases.